Ion‐Mobility Mass Spectrometry for the Rapid Determination of the Topology of Interlocked and Knotted Molecules. Issue 33 (10th July 2019) - Kruve, Anneli; Caprice, Kenji; Lavendomme, Roy; Wollschläger, Jan M.; Schoder, Stefan; Schröder, Hendrik V.; Nitschke, Jonathan R.; Cougnon, Fabien B. L.; Schalley, Christoph A.
Abstract: A rapid screening method based on traveling‐wave ion‐mobility spectrometry (TWIMS) combined with tandem mass spectrometry provides insight into the topology of interlocked and knotted molecules, even when they exist in complex mixtures, such as interconverting dynamic combinatorial libraries. A TWIMS characterization of structure‐indicative fragments generated by collision‐induced dissociation (CID) together with a floppiness parameter defined based on parent‐ and fragment‐ion arrival times provide a straightforward topology identification. To demonstrate its broad applicability, this approach is applied here to six Hopf and two Solomon links, a trefoil knot, and a [3]catenate. Abstract : Cutting the Gordian knot : Collision‐induced dissociation and travelling‐wave ion‐mobility mass spectrometry together provide a fast screening method to identify the topology of molecular Hopf and Solomon links, a [3]catenate, and a trefoil knot, even when they coexist in quickly equilibrating dynamic combinatorial libraries.